Karen Hulene Bartell: The Best of Taiwanese Cuisine - Jaine, Tom (Petits Propos Culinaires, 2024)
Karen Hulene Bartell: The Best of Taiwanese Cuisine: Hippocrene Books, New York, 2001: ISBN 0-7818-0855-3: 122 pp., b/w illus., h/b, $24.95.